Advancements in 3d concrete printing materials - Lamb Cannon; Sabih Gauhar (MATEC Web of Conferences)
3D concrete printing (3DCP) is a promising technology with the potential to revolutionize the construction industry by automating the fabrication of complex structures in a more efficient, sustainable, and design-oriented manner. It will also help address the growing labour shortage in the construction industry by automating tasks and increasing productivity. But 3DCP will only succeed if we are able to find and optimize printing material: materials such as the typical materials used in concrete to the more uncommon materials that have recently become available. This review will explore 3D concrete printing materials development which is a lynchpin in implementing 3DCP to the market. This review examines challenges in identifying suitable 3DCP materials, including limitations of traditional mixes, the performance of various cementitious materials and admixtures, and the effectiveness of different pumping systems.